Exploring different product-service combinations for sustainable clothing rental service based on consumer preferences and climate change impacts - Eri Amasawa; Koji Kimita; Tatsuki Yoshida; Masahiko Hirao (Scientific Reports)
Abstract Access-based consumption of clothing has garnered attention because of its sustainability potential; however, the profile of a product-service combination that benefits both consumers and the environment has been inconclusive. To characterize these services, this study explored consumer preferences and climate change impact of diverse garment type and service combinations for a clothing rental service. We performed a web-based survey in Japan to analyze consumer preferences and intended behavior for 15 garment types and ten service types in clothing rentals. The survey results were used to characterize the desired clothing rental service using a cluster analysis and to calculate life cycle greenhouse gas emissions when the garment was purchased and rented. The results showed a specific combination of consumer segments, product characteristics, and service types that construct a sustainable clothing rental service; formal dress, dress shirt, and maternity wear were the garment types that would reduce greenhouse gas emissions by 21% ~ 75% depending on consumer behavior and service implementation. We also demonstrate that implementing services often augments greenhouse gas emissions. This study conveys that renting garments for occasional wear are ideal for both consumers and the environment, and rental service providers need to effectively manage product’s lifetime extension.